Workplace mental health training for managers and its effect on sick leave in employees: a cluster randomised controlled trial. (November 2017) - Milligan-Saville, Josie S; Tan, Leona; Gayed, Aimée; Barnes, Caryl; Madan, Ira; Dobson, Mark; Bryant, Richard A; Christensen, Helen; Mykletun, Arnstein; Harvey, Samuel B
Summary: Background: Mental illness is one of the most rapidly increasing causes of long-term sickness absence, despite improved rates of detection and development of more effective interventions. However, mental health training for managers might help improve occupational outcomes for people with mental health problems. We aimed to investigate the effect of mental health training on managers' knowledge, attitudes, confidence, and behaviour towards employees with mental health problems, and its effect on employee sickness absence. Methods: We did a cluster randomised controlled trial of manager mental health training within a large Australian fire and rescue service, with a 6-month follow-up. Managers (clusters) at the level of duty commander or equivalent were randomly assigned (1:1) using an online random sequence generator to either a 4-h face-to-face RESPECT mental health training programme or a deferred training control group. Researchers, managers, and employees were not masked to the outcome of randomisation. Firefighters and station officers supervised by each manager were included in the study via their anonymised sickness absence records. The primary outcome measure was change in sickness absence among those supervised by each of the managers. We analysed rates of work-related sick leave and standard sick leave seperately, with rate being defined as sickness absence hours divided by the sum of hours of sickness absence and hours of attendance. This trial was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12613001156774). Findings: 128 managers were recruited between Feb 18, 2014, and May 17, 2014. 46 (71%) of 65 managers allocated to the intervention group received the intervention, and 42 (67%) of 63 managers allocated to the control group were entered in the deferred training group. Managers and their employees were followed up and reassessed at 6 months after randomisation. 25 managers (1233 employees) in the intervention group and 19 managers (733 employees) in the control group provided data for the primary analysis. During the 6-month follow-up, the mean rate of work-related sick leave decreased by 0·28 percentage points (pp) from a pre-training mean of 1·56% (SE 0·23) in the intervention group and increased by 0·28 pp from 0·95% (0·20) in the control group (p=0·049), corresponding to a reduction of 6·45 h per employee per 6 months. The mean percentage of standard sick leave increased by 0·48 pp from 4·97% (0·22) in the intervention group and by 0·31 pp from 5·27% (0·21) in the control group (p=0·169). Interpretation: A 4-h manager mental health training programme could lead to a significant reduction in work-related sickness absence, with an associated return on investment of £9.98 for each pound spent on such training. Further research is needed to confirm these findings and test their applicability in other work settings. Funding: NSW Health and Employers Mutual Ltd.